A systematic review of the effects of bisphenol analogs on embryonic development and cytoskeletal organization of zebrafish Danio rerio embryos - Dasiman, Razif; Md Nor, Norazmir; Eshak, Zolkapli; Mohd Mutalip, Siti Syairah; Suwandi, Nur Rohmah; Bidin, Habsah; Abas, Razif (AMG Transcend Association, 2021)
Recent research has raised concerns about widespread exposure to chemicals that resemble bisphenol A (BPA) structurally or functionally. Because of the strict regulations governing production and use, various bisphenol analogs to replace BPA have increased. Some analogs have been reported to have disruptive physiological and endocrine effects. This study focuses on the impact of bisphenol A analogs on zebrafish embryos. The effect of bisphenol analogs is a major concern, prompting researchers to conduct numerous related studies. Regrettably, previous research has not focused on embryonic health. A systematic search strategy based on the RepOrting Standards for Systematic Evidence Syntheses (ROSES) guidelines was used. Three central journal repositories were used: Scopus, Web of Science, and ScienceDirect. Thirteen articles were discovered through search efforts and will be thoroughly examined. Bisphenol analogs were unearthed to have similar adverse effects on embryonic health as bisphenol-A. This study clarified how bisphenol A analogs affect embryonic development and cytoskeletal organization in the zebrafish model by disrupting the endocrine, cardiovascular, nervous, reproductive, and other systems. To thoroughly investigate these issues, more research on each source, metabolic pathway, exposure mechanisms, and effects on organisms is required.